Astatine-211 imaging by a Compton camera for targeted radiotherapy. (September 2018) - Nagao, Yuto; Yamaguchi, Mitsutaka; Watanabe, Shigeki; Ishioka, Noriko S.; Kawachi, Naoki; Watabe, Hiroshi
Abstract: Astatine-211 is a promising radionuclide for targeted radiotherapy. It is required to image the distribution of targeted radiotherapeutic agents in a patient's body for optimization of treatment strategies. We proposed to image 211 At with high-energy photons to overcome some problems in conventional planar or single-photon emission computed tomography imaging. We performed an imaging experiment of a point-like 211 At source using a Compton camera, and demonstrated the capability of imaging 211 At with the high-energy photons for the first time. Highlights: We proposed to image 211 At with high-energy photons. An 211 At imaging experiment using a developed Compton camera was performed. We demonstrated the capability of imaging 211 At by the proposed method.